Structural Composition of the AUX (Auxiliary) in English and Indonesian: A Contrastive Grammatical Analysis - Abdul Hadi (Indonesian Journal of Integrated English Language Teaching, 2022)
There are significant linguistic differences between English and Indonesian despite the fact that modern Indonesian adopts the Roman script in its writing system. Unlike English, Indonesian is most probably a language without tenses, or if it has tense(s), no single element of its auxiliary rules will be affected by the tense(s). Language component-wise, the differences in vocabulary, pronunciation, and grammar are obvious between the two languages. In grammar, the structural composition of the AUX (Auxiliary) in Indonesian is heavily based on function words (sedang, akan, and other equivalents of Modals in English). These function words remained unchanged whatever the tense of the sentences is. English, on the other hand, is significantly affected by its structural composition of the AUX. Therefore, it takes quite significant time for Indonesian learning English to get used to the usage of English auxiliary system as it is much more complicated than Indonesian auxiliary system. Conversely, English speakers learning Indonesian most probably will find the structural composition of the AUX in Indonesian fairly simple to master.